2000
DOI: 10.1086/317847
|View full text |Cite
|
Sign up to set email alerts
|

Keck Mid‐Infrared Imaging of QSO 2237+0305

Abstract: Using the Long Wavelength Spectrometer on Keck, we have imaged the gravitationally lensed radioquiet quasi-stellar object QSO 2237]0305 at 8.9 and 11.7 km for the Ðrst time. The mid-IR Ñux ratios are inconsistent with the optical Ñux ratios but agree with the radio Ñux ratios and with some published gravitational lens models. These Ñux ratios indicate that the IR emission is not a †ected by microlensing, which rules out the synchrotron emission model. The IR emission is likely produced by hot dust extended on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(104 citation statements)
references
References 50 publications
10
92
2
Order By: Relevance
“…In particular the magnitude difference as a function of wavelength for the epoch HJD 2454001 (Figure 1(c)) is flat given our errors of the order of ∼0.1 mag. This suggests a smaller differential extinction than the estimates of Agol et al (2000), although we cannot rule out fortuitous cancellations of color variations due to extinction by chromatic microlensing effects. Finding chromatic microlensing during this period of observations is not a surprise, since the Optical Gravitational Lensing Experiment V-band continuum data (Woźniak et al 2000) shows significant brightness variations in the three independent magnitude differences at this time.…”
Section: Observations and Data Analysiscontrasting
confidence: 62%
“…In particular the magnitude difference as a function of wavelength for the epoch HJD 2454001 (Figure 1(c)) is flat given our errors of the order of ∼0.1 mag. This suggests a smaller differential extinction than the estimates of Agol et al (2000), although we cannot rule out fortuitous cancellations of color variations due to extinction by chromatic microlensing effects. Finding chromatic microlensing during this period of observations is not a surprise, since the Optical Gravitational Lensing Experiment V-band continuum data (Woźniak et al 2000) shows significant brightness variations in the three independent magnitude differences at this time.…”
Section: Observations and Data Analysiscontrasting
confidence: 62%
“…According to the macromodel by Schmidt et al (1998), rather well confirmed by the observations in emission lines (Fitte & Adam 1994;Racine 1992;Lewis et al 1998;Saust 1994), and in the IR spectral range (Nadeau et al 1991;Agol et al 2000), where no microlensing effects are expected, the A, B and D components must be almost equally amplified, with flux ratios of 0.25, 0.27 and 0.32 respectively. The C component is expected to have the lowest macroamplification factor by this model, a flux ratio of 0.15 is predicted for it.…”
Section: Variations Of Color In Q2237+0305mentioning
confidence: 56%
“…By this time, a great amount of observations of Q2237+0305 in spectral ranges other than visual continuum exists -VLA observations at 20 cm and 3.6 cm (Falco et al 1996), observations in the near and mid-IR (Nadeau et al 1991;Agol et al 2000), and in the quasar emission lines (Fitte & Adam 1994;Racine 1992;De Robertis & Yee 1988;Lewis et al 1998;Saust 1994). The observed magnitudes of the components have been found to be almost unaffected by microlensing in these spectral ranges, which indicates that much larger quasar features radiate in IR and in the radio, as well as in the emission lines, compared to the optical continuum.…”
Section: Introductionmentioning
confidence: 99%
“…The optical data were taken from Wozniak et al (2000), and corrected for extinction. The analysis of the 1999 data is described in Agol et al (2000). The 2000 data had Poisson errors since the pattern noise was eliminated.…”
Section: Observationsmentioning
confidence: 99%